Do meat anti-consumption opinions influence consumers' wellbeing?–The moderating role of religiosity - Xie, Ling; Shahzad, Muhammad Faisal; Waheed, Abdul; Ain, Qurat ul; Saleem, Zunair; Ali, Mehwish Asghar (Frontiers in Psychology, 2022)
The study aimed to determine the role of personal factors, consumer social responsibility, and sensitivity to social marketing among meat anti-consumers. The study constructs and tests a model of anti-consumption, using a sample of (n=597) collected from a cluster of young consumers using a survey questionnaire. SEM using AMOS model 1 followed by the Johnson-Neyman technique testing moderation was used Results specify religiosity as the moderating driver of anti-consumption of meat among young consumers in Pakistan. Consumer social responsibility is a strong antecedent, while social marketing is significantly documented for sustainability motives. Consumers report the personal health and environmental domain as an encouraging element for meat anti-consumption. The study uncovers social marketing motivations for anti-consumption and, in so doing, guides marketers and policymakers in their targeting and planning. The study is the first to establish the moderating role of religious motivations and meat anti-consumption behavior among Muslim consumers to achieve healthy well-being.